Methanation of CO2 Using MIL-53-Based Catalysts: Ni/MIL-53–Al2O3 versus Ni/MIL-53 - Oana Grad (MDPI AG, 2021)
MIL-53 and the MIL-53–Al2O3 composite synthesized by a solvothermal procedure, with water as the only solvent besides CrCl3 and benzene-1,4-dicarboxylic acid (BDC), were used as catalytic supports to obtain the novel MIL-53-based catalysts Ni(10 wt.%)/MIL-53 and Ni(10 wt.%)/MIL-53–Al2O3. Ni nanoparticle deposition by an adapted double-solvent method leads to the uniform distribution of metallic particles, both smaller (≤10 nm) and larger ones (10–30 nm). MIL-53–Al2O3 and Ni/MIL-53–Al2O3 show superior thermal stability to MIL-53 and Ni/MIL-53, while MIL-53–Al2O3 samples combine the features of both MIL-53 and alumina in terms of porosity. The investigation of temperature’s effect on the catalytic performance in the methanation process (CO2:H2 = 1:5.2, GHSV = 4650 h−1) revealed that Ni/MIL-53 is more active at temperatures below 300 °C, and Ni/MIL-53–Al2O3 above 300 °C. Both catalysts show maximum CO2 conversion at 350 °C: 75.5% for Ni/MIL-53 (methane selectivity of 93%) and 88.8% for Ni/MIL-53–Al2O3 (methane selectivity of 98%). Stability tests performed at 280 °C prove that Ni/MIL-53–Al2O3 is a possible candidate for the CO2 methanation process due to its high CO2 conversion and CH4 selectivity, corroborated by the preservation of the structure and crystallinity of MIL-53 after prolonged exposure in the reaction medium.